A new genus and three new species of eriophyoid mites from New Zealand Coprosma (Rubiaceae) - Han, Xiao; Zhang, Zhi-Qiang (Zootaxa, 2019)
A new genus and three new species of eriophyoid mites of the family Eriophyidae are described and illustrated from various Coprosma species in New Zealand: Calareolata gen. nov., Calareolata coprosmae sp. nov., Cosetacus mamangi sp. nov. and Aculus robustalucidus sp. nov.. A key to the eriophyoid mites associated with Coprosma species in the world is provided.